Reforming India’s Labor Laws: Ensuring Social Security for Gig Workers in the Digital Economy - Prakash, Nidhi (Trinity Law Review, 2025)
The rapid growth of the gig economy in India has transformed the labor landscape, offering flexible work opportunities but also leaving gig workers without sufficient legal safeguards. This paper critically analyzes the legal status of gig workers in India, highlighting their exclusion from traditional labor protections and the challenges they face in accessing social security benefits. Through secondary data analysis and case studies, including a focus on YouTube content creators, the study examines issues such as inconsistent income, lack of healthcare coverage, and the absence of formal mechanisms for unionization, all of which contribute to economic insecurity among gig workers. The research reveals that the Code on Social Security, 2020 falls short in providing comprehensive protections for gig workers, with notable gaps in areas such as health insurance, pension plans, and job security. By comparing India’s current approach to global models in regions like the European Union, California, and Australia, the paper identifies key policy lessons that could improve worker protections. The findings suggest the need for greater integration of gig workers into India’s formal labor system, accompanied by policy recommendations aimed at enhancing worker welfare, ensuring platform accountability, and fostering a more inclusive digital economy. This paper contributes to ongoing discussions on labor rights in the gig economy, offering insights into how India can develop a more equitable framework for gig workers.